CHARACTERISTICS OF THE EXPRESSION OF THE CUV LEXEMA FROM THE DENOTATIVE SEMANTICS OF ITS "QUALIFIC KNOWLEDGE" AND CLASSICAL SOURCES - Ma`suma Mominova (Academia Science Repository, 2023)
In this article, a classification of the meanings of the lexeme water given in the "Explanatory Dictionary of the Uzbek Language" according to the cultural code symbol ownership/non-ownership was developed based on the classification of the units with the "water" component of a simple structure and their linguistic-cultural characteristics. Based on the denotative semantics of the lexeme Cuv, its expression in "Kutadgu Bilig" and classical sources was also touched upon.